2010
DOI: 10.1179/174313209x455718
|View full text |Cite
|
Sign up to set email alerts
|

A gene delivery system with a human artificial chromosome vector based on migration of mesenchymal stem cells towards human glioblastoma HTB14 cells

Abstract: Mesenchymal stem cells (MSCs) have been expected to become useful gene delivery vehicles against human malignant gliomas when coupled with an appropriate vector system, because they migrate towards the lesion. Human artificial chromosomes (HACs) are non-integrating vectors with several advantages for gene therapy, namely, no limitations on the size and number of genes that can be inserted. We investigated the migration of human immortalized MSCs bearing a HAC vector containing the herpes simplex virus thymidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…Likewise NSC, mesenchymal stem cells (MSC) migrate towards glioma lesions and may be taken into consideration as gene delivery vehicles against human malignant gliomas [25]. Human bone marrow-derived MSC (hMSC) have been used as a cellular vehicle for the targeted delivery and local production of TRAIL at the glioma tumour site [26].…”
Section: Use As Gene Delivery Vehiclementioning
confidence: 99%
“…Likewise NSC, mesenchymal stem cells (MSC) migrate towards glioma lesions and may be taken into consideration as gene delivery vehicles against human malignant gliomas [25]. Human bone marrow-derived MSC (hMSC) have been used as a cellular vehicle for the targeted delivery and local production of TRAIL at the glioma tumour site [26].…”
Section: Use As Gene Delivery Vehiclementioning
confidence: 99%
“…Esto disminuiría la anormal tolerancia del tumor y favorecería la inmunidad, tanto contra las células tumorales que expresan B7, como contra las células del tumor original. 46,47 Éstas y otras estrategias se han ensayado frente a diferentes neoplasias, como cáncer de ovario, 48,49 melanoma, 50-52 cáncer de mama, 50 glioblastoma, 53,54 carcinoma hepatocelular 55 y neuroblastoma, 56 entre muchas otras. Cabe destacar que, al día de hoy, los protocolos oncológicos de TG están dirigidos a pacientes con metástasis, más que contra las neoplasias primarias.…”
Section: Aumento De La Inmunogenicidad Del Tumorunclassified
“…Recently, HSV-tk-engineered MSCs in combination with systemic administration of ganciclovir have been used in the treatment of C6 glioma (Amano et al, 2009;Uchibori et al, 2009;Chang et al, 2010) and Panc02 pancreatic cancer (Zischek et al, 2009). When coupled with the HSV-tk-ganciclovir prodrug cancer gene therapy system, with delivery by either implantation into the opposite hemisphere or injection into xenografts, EC-MSCs have been demonstrated to inhibit U87 and HTB14 tumor growth and to prolong the survival of mice (Kinoshita et al, 2010;Bak et al, 2011;de Melo et al, 2015). Additionally, Matuskova et al (2010) have demonstrated the formation of gap junctions between AT-MSCs and human glioblastoma cells (8-MG-BA, 42-MG-BA, and U-118).…”
Section: Msc Delivery Of Virusesmentioning
confidence: 99%